A Computational Model of Dengue Transmission by Cellular Automata - Pino Romero, Neisser (2019)
The research paper presents a computational model by Cellular Automata (Cell-DEVS) applied to the transmission of Dengue disease, spread by mosquitoes to a susceptible population. This model will have a multilevel approach to consider exogenous interactions such as temperature. This will allow to be able to visualize the critical points where the mosquito reproduction is much greater, and thus carry out control strategies.